Implementasi Kinerja Guru Dalam Meningkatkan Mutu Hasil Belajar - Suanto; Lestari, Yulita Puji (Prodi PPKn FKIP Universitas Pamulang, 2025)
Teacher performance is one of the key factors in the learning process that has a direct impact on the quality of student learning outcomes. In the context of increasingly competitive education, improving the quality of the learning process has a very crucial role in achieving optimal educational goals. Although many efforts have been made to improve teacher performance, there are still challenges in implementing effective learning strategies. This has the potential to hinder the achievement of expected learning outcomes. This study aims to analyze the implementation of teacher performance and its impact on student learning outcomes, as well as to identify factors that influence teacher performance. The method used in this study is a qualitative approach with data collection techniques through interviews, observations, and documentation studies. The subjects of the study included teachers and students in several schools. The results of the study indicate that good teacher performance, including mature learning planning, the use of varied teaching methods, and appropriate evaluation, contribute significantly to improving student learning outcomes. The implementation of effective teacher performance greatly affects student learning outcomes. Improving teacher competence through training and professional development needs to be done continuously. It is recommended that schools and the government provide more support in the form of adequate teacher training to improve teacher performance, as well as conducting periodic monitoring and evaluation of the learning process.